2023
DOI: 10.1063/5.0144701
|View full text |Cite
|
Sign up to set email alerts
|

Time and temperature dependent magnetic viscosity experiments on Sr/Co nanoferrite particles

Abstract: Magnetic viscosity experiments have been performed in order to investigate the magnetization reversal in Sr nanoferrite particles (nanoscale SrFe12O19) and interacting Sr/Co nanoferrite particles (SrFe12O19–CoFe2O4 nanocomposites). The magnetic viscosity S = d M ( t ) / d l n ( t ), where M ( t ) is the magnetization as a function of time, has been collected. For Sr nanoferrite S shows a maximum close to the coercive field, reflecting the relation between S and the energy barrier distribution. We evidence that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In this aspect it is important to note that these values of V a are similar to those obtained and previously reported for Sr-M and other hexaferrites. [14,30,41,42] Although the activation volume for the ceramic sample is larger than for the Bacop, when compared to its particle size, it constitutes a much smaller part of it.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this aspect it is important to note that these values of V a are similar to those obtained and previously reported for Sr-M and other hexaferrites. [14,30,41,42] Although the activation volume for the ceramic sample is larger than for the Bacop, when compared to its particle size, it constitutes a much smaller part of it.…”
Section: Resultsmentioning
confidence: 99%
“…However, this behavior for V a is also confirmed in the ceramic sample, in which a coherent rotation mechanism cannot be considered because the particle diameter is well above the critical singledomain diameter. If the activation volume notion is, not only "the volume of material involved in a single activation" [31][32][33][34] , but also "the smallest volume of material that reverses coherently in an event", [42] we would expect that this activation volume follows the temperature behavior of the single-domain diameter. Then, even in ceramic samples, it would appear that the departure from saturation occurs in a uniform-moment configuration nucleated volume.…”
Section: Resultsmentioning
confidence: 99%
“…In single domain particles, the magnetic viscosity extracted from the time dependence of magnetization S = ∂M/∂lgt can be presented as a logarithmic derivative of the magnetic susceptibility [23]: It was shown that the same formula is applicable for polycrystalline materials as well if an additional correction coefficient assuming intergrain interaction is introduced. This formula proposed by Neel establishes an interrelation between magnetic viscosity and a frequency derivative of magnetic susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…6(c) and (d) the hysteresis loops at 300 and 5 K for the weighted sum (i.e., superposition)of SFO@pH10 and annealed CZFO seeds (with the corresponding weight ratio), and the experimental loops for NC@CZFO@pH10 as a reference. We should keep in mind that we expect the anisotropy of CZFO to increase as temperature is lowered, while the anisotropy of SFO decreases, 60 and thus the critical size for effective coupling changes significantly. 61 Even if CZFO phases grow differently whether in the composite or individually (see Section 8 of ESI †), at 5 K it is evident (despite the low concentration of CZFO, 7 wt%) that the hysteresis for the superposition shows a double-loop response, typical of mixtures/phase-segregated systems.…”
Section: Magnetic Couplingmentioning
confidence: 99%